PWE-095 Cost effectiveness of rifaximin-α 550 mg (xifaxan®/targaxan®) in the reduction of recurrence of overt hepatic encephalopathy in united kingdom. (22nd June 2015) - Berni, E; Poole, CD; Conway, P; Radwan, A; Currie, CJ
Abstract : Introduction: Hepatic encephalopathy (HE) is associated with high morbidity and mortality. Rifaximin-α 550 mg (XIFAXAN®/TARGAXAN®) is effective in reducing the recurrence of episodes of overt HE. Our aim was to determine the cost effectiveness of rifaximin-α 550 mg versus standard care (lactulose) in patients with cirrhosis in the UK. Method: This economic evaluation used a Markov state transition model. The outcome metric was the incremental cost effectiveness ratio (ICER), derived from estimates of the cost/quality adjusted life years (QALYs). The payer perspective was that of UK National Health Service. Outcome data were from two trials of rifaximin-α 550 mg. Population outcome data were from a complementary study of patients with liver cirrhosis treated within the NHS. UK Costs data (2012) were derived from published sources. Health-related utility was estimated indirectly from disease-specific quality of life RCT data. The time horizon was five years. Costs and benefits were discounted at 3.5%. Extensive sensitivity analyses were carried out. Real world data describing the use of rifaximin-α 550 mg in the UK NHS were also applied into the model for length of stay in hospital and the number of admissions. Results: The average cost for the included elements of care was £22, 971 in the rifaximin-α 550 mg arm and £23, 545 in the lactulose arm, a difference of -£573. The corresponding values for benefit were 2.56 QALYs and 1.75 QALYs per person, respectively, a difference of 0.81 QALYs. This translated into a dominant base-case ICER. Key parameters that impacted the ICER included length of stay in hospital and the number of admissions to hospital. Evaluation to 10 years and lifetime resulted in ICERs of £3, 024/QALY and £5, 068/QALY, respectively. Conclusion: Rifaximin-α 550 mg in patients with recurrent HE in the context of liver cirrhosis represented good value for money compared to standard care, by reducing episodes of overt HE, the likelihood of hospital admission and hospital length of stay. This analysis was funded by Norgine. Disclosure of interest: E. Berni Consultant for: Norgine, C. Poole Consultant for: Norgine, P. Conway Employee of: Norgine, A. Radwan Employee of: Norgine, C. Currie Consultant for: Norgine.